Relativistic quantum dynamics of a spin-0 massive charged particle in the presence of external fields in a Gödel-type space-time with Coulomb potentials and Aharonov–Bohm effect - Ahmed, Faizuddin (European physical journal plus, 2020)
In this paper, we investigate the relativistic quantum dynamics of spin-0 massive charged particles in the presence of an external field in a Gödel-type space-time with potentials. We derive the radial wave equation of the Klein–Gordon equation with an external uniform magnetic field including a magnetic quantum flux subject to a Coulomb-type scalar and vector potentials in the background of the Som–Raychaudhuri space-time with a cosmic string. We solve this radial wave equation and evaluate the energy eigenvalues and eigenfunctions and analyze a relativistic analogue effect of the Aharonov–Bohm effect for bound states.